A case–control study of agricultural and behavioral factors associated with leptospirosis in Vietnam - Luu Phuong Dung; Pham Thanh Hai; Luong Minh Hoa; Tran Ngoc Phuong Mai; Nguyen Thi My Hanh; Phan Dang Than; Van Dinh Tran; Nguyen Tu Quyet; Hoang Hai; Do Bich Ngoc; Nguyen Thị Thu; Le Thi Phuong Mai (BMC Infectious Diseases, 2022)
Abstract Introduction Leptospirosis is a neglected disease in Vietnam. Until now, there has been limited knowledge about risk factors of this disease in Vietnam. The study was carried out to identify agricultural and behavioral factors associated with the transmission of leptospirosis in Vietnam. Methods This matched retrospective hospital-community-based case–control study was conducted from 1 October 2018 to 31 October 2019. We recruited cases from 11 selected government hospitals in three provinces of Vietnam, while controls were selected from the same communes of cases and matched by age (± 2 years) and sex. Microscopic agglutination test (MAT) and enzyme-linked immunosorbent assay (ELISA) were applied to determine confirmed cases, while only MAT was used to identify controls with a single high MAT titer < 1:100. Results 504 participants (252 cases and 252 controls) were identified. Cultivating (OR 2.83, CI 1.38–5.79), animal farming (OR 8.26, CI 2.24–30.52), pig owners (OR 10.48, CI 5.05–21.73), cat owners (OR 2.62, CI 1.49–4.61) and drinking unboiled water (OR 1.72, CI 1.14 –2.59, p = 0.010) were significantly associated with human leptospirosis in Vietnam. Hand washing after farming/ gardening (OR 0.57, CI 0.38–0.86, p = 0.007) and bathing after farming, gardening, contact with cattle and poultry (OR 0.33, CI 0.19–0.58, p = 0.000) were determined as protective factors for this disease. Conclusions In short, the case–control study has revealed the risks in agricultural and animal practices and protective behavioral factors related to human leptospirosis in Vietnam. The findings suggested promotion of communication and health education programs targeting health behaviors in daily life and agricultural practices. Using personal protective equipment such as gowns, gloves, and boots during agricultural practices, especially cultivating and animal farming, is most recommended.